Effect of various levels of Ralgro on reproductive performance of yearling heifers - Corah, L.; Sprott, L.R.; Francis, G.; Kiracofe, G. (Kansas State University. Agricultural Experiment Station, 2011)
Implanting heifers at weaning time with 12, 24, or 36 mg of Ralgro did not affect reproductive performance of the heifers when bred as yearlings.
Keywords: Beef; Reproductive performance; Yearling heifers